2005
DOI: 10.1203/01.pdr.0000188699.55279.1b
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of Respiratory Syncytial Virus to Pneumococci: A Phenomenon That Enhances Both Pneumococcal Adherence to Human Epithelial Cells and Pneumococcal Invasiveness in a Murine Model

Abstract: In a previous study we showed that pneumococcal adherence to epithelial cells was enhanced by a preceding respiratory syncytial virus (RSV) infection. RSV-glycoproteins, expressed on the infected cell surface, may play a role in this enhanced pneumococcal binding, by acting as bacterial receptors. In the current study, it was attempted to analyze the capacity of pneumococci to interact directly with RSV virions. By flowcytometry, a direct interaction between RSV and pneumococci could be detected. Heparin, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 27 publications
2
100
1
2
Order By: Relevance
“…Next to increased expression of host receptors, viral proteins displayed on the cell surface can enhance adherence and internalization of bacteria. The RSV attachment glycoprotein (G) protein, present on the surface of either RSV virions or infected cells, can serve as a binding structure for non-typeable H. influenzae (Avadhanula et al, 2007), S. pneumoniae (Avadhanula et al, 2007;Hament et al, 2005) and Pseudomonas aeruginosa (Van Ewijk et al, 2007). Similarly, integration of influenza virus haemagglutinin into the cell membrane of infected cells facilitates attachment and invasive disease of group A streptococci in mice (Okamoto et al, 2003).…”
Section: Receptor Expressionmentioning
confidence: 99%
“…Next to increased expression of host receptors, viral proteins displayed on the cell surface can enhance adherence and internalization of bacteria. The RSV attachment glycoprotein (G) protein, present on the surface of either RSV virions or infected cells, can serve as a binding structure for non-typeable H. influenzae (Avadhanula et al, 2007), S. pneumoniae (Avadhanula et al, 2007;Hament et al, 2005) and Pseudomonas aeruginosa (Van Ewijk et al, 2007). Similarly, integration of influenza virus haemagglutinin into the cell membrane of infected cells facilitates attachment and invasive disease of group A streptococci in mice (Okamoto et al, 2003).…”
Section: Receptor Expressionmentioning
confidence: 99%
“…The RSV G glycoprotein has previously been shown to act as a receptor for S. pneumoniae adherence, thus promoting pneumococcal colonisation of the airways (128,136,137). RSV has also been shown to enhance pneumococcal virulence in animal models, with co-infection resulting in increased inflammation (128,137,262).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies suggests that RSV may trigger an outgrowth of S. pneumoniae from the URT flora through promotion of bacterial adherence and disruption of bacterial clearance mechanisms (128,138,140,262). However, we have previously hypothesised that, since RSV virion and S. pneumoniae complexes have been shown to form (128,136,137), these complexes may be co-transmitted in respiratory secretions, particularly in settings of rapid transmission such as childcare centres (6). Longitudinal studies with samples taken before, during and after an RSV infection within the same participant may represent the best way to differentiate between these hypotheses, however, to date such longitudinal studies have focused on characterising the nasopharyngeal microbiota, and have only shown increases in abundance of the Streptococcus genus during viral ARI, without species-level resolution and without reporting changes in abundances surrounding an ARI episode within individuals (5, 18).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations